2016
DOI: 10.1055/s-0042-109777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direction and Tension of Kinesio Taping Application on Sensorimotor Coordination

Abstract: The present study investigates whether different directions and tensions of Kinesio(®) Tex tape (KT) application differently influence the precision of sensorimotor synchronization, defined as the ability to coordinate actions with predictable external events. 10 healthy participants performed sets of repetitive wrist flexion-extensions synchronized to a series of paced audio stimuli with an inter-onset interval (IOI) of 500 and 400 ms. KT was applied over the wrist and finger extensor muscles. 2 facilitatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 39 publications
3
52
0
1
Order By: Relevance
“…Similar to other investigations on the influence of KNT tension or convolutions, 6,8 we found that neither tension nor convolutions of KNT altered skin blood flow. Cumulatively, our data and those of others suggest that the vasoactive and analgesic properties of KNT are inherent to KNT application and not because of a specific method of application.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to other investigations on the influence of KNT tension or convolutions, 6,8 we found that neither tension nor convolutions of KNT altered skin blood flow. Cumulatively, our data and those of others suggest that the vasoactive and analgesic properties of KNT are inherent to KNT application and not because of a specific method of application.…”
Section: Discussionsupporting
confidence: 91%
“…Bravi et al found that KNT improved sensorimotor coordination regardless of application tension, noting that there was no difference in performance when KNT was applied at either 25% or 50% relative tension. 8 In a systematic review, Lim and Tay found that the effect size for KNT-mediated pain reduction reduced when KNT was applied at higher tensions. 9 The importance of KNT tension or convolutions in facilitating skin blood flow is yet to be determined.…”
Section: Methodsmentioning
confidence: 99%
“…The setup is the same we used in our previous works [3][4][5][6][7] and is here summarized. Every participant was tested individually, sitting upright on a chair with the feet on leg rest.…”
Section: Setupmentioning
confidence: 99%
“…The KT efficacy on this population, that did non really have any functional problems to report, was frequently found to be null or minimal. However, in our previous studies that investigated the effect of KT application on timing coordination [4,6], we showed that temporal precision of repeated isochronous wrist's flexion-extensions (IWFEs) was increased by KT application in healthy young subjects, thus demonstrating that the normal population may show a benefit from elastic tape when tested under specific circumstances. We argued that the augmented timing consistency of IWFEs was determined by a more efficient wrist joint motor control during movements due to an extra-proprioceptive effect provided by KT [4,6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation